Implementation of Fuzzy Logic Using The Tsukamoto Method to Forecast Gold Price in Indonesia - Alviari, Irfaliani; Monika, Ines; Sarina, Sarina; Saputra, Lianda; Prayanti, Baiq Desy Aniska (University of Mataram, 2025)
In the economy, gold is a commodity that has an important role. This indicates that gold is often used as an investment for investors and people involved in the business world. This research aims to determine how accurate gold price forecasting is using the Tsukamoto fuzzy method in Indonesia. Gold prices are influenced by several factors. These factors include exchange rates, interest rates, inflation, etc. Based on research results, fuzzy Tsukamoto determined the price of gold with a forecasting truth value of 99.91611654% and a MAPE value of 0.083883458%. The conclusion of this research is forecasting gold prices using the Tsukamoto fuzzy method is considered very good.